APPLICATION OF LOW-COST PARTICULATE MATTER SENSORS FOR MEASUREMENT OF POLLUTANTS GENERATED DURING 3D PRINTING - Tatarczak, Jarosław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
This work presents measurement results of pollutants generated during 3D printing. The measure of pollutants is the concentration of particulate matter with a diameter of up to 2.5 μm (PM2,5). Materials acrylonitrile-butadiene-styrene (ABS), polyactide (PLA) for a 3D printer and low-cost particulate matter concentration sensors PMS3003, PMS7003 were used in the research. Research results show that low-cost sensors can be useful for monitoring pollution during 3D printing in offices, laboratories or private homes.